1985
DOI: 10.1007/bf00634252
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nicotine and cytisine on3H-acetylcholine release from cortical slices of guinea-pig brain

Abstract: Nicotine 1.8 X 10(-5)-1.8 X 10(-4) mol/l enhanced the spontaneous 3H-efflux from guinea-pig cortical slices preloaded with 3H-choline and perfused in the presence of hemicholinium (HC-3). The facilitation of tritium outflow was prevented by tetrodotoxin 5 X 10(-7) mol/l and by D-tubocurarine 4.5 X 10(-6) mol/l. Nicotine 1.8 X 10(-6)-1.8 X 10(-4) mol/l, and the agonist cytisine 5 X 10(-7)-5 X 10(-5) mol/l increased, in a concentration-dependent way, 3H-efflux from electrically-stimulated slices (0.2 Hz). The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
2

Year Published

1987
1987
2012
2012

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 14 publications
2
25
2
Order By: Relevance
“…A positive correlation between number of high affinity nicotinic receptors and 3H-ACh release has also been observed (Nordberg et al, 1987 a). It is known from studies on animal tissues that the effect of agonist activity on nicotinic receptors can only be measured after short exposure time, since longer exposure times cause a desensitization of the nicotinic receptors (Beani et al, 1985). In control human brain tissue, an increased ACh content in the synaptic cleft induced by cholinesterase inhibitors, may induce desensitization of the presynaptically located nicotinic receptors.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…A positive correlation between number of high affinity nicotinic receptors and 3H-ACh release has also been observed (Nordberg et al, 1987 a). It is known from studies on animal tissues that the effect of agonist activity on nicotinic receptors can only be measured after short exposure time, since longer exposure times cause a desensitization of the nicotinic receptors (Beani et al, 1985). In control human brain tissue, an increased ACh content in the synaptic cleft induced by cholinesterase inhibitors, may induce desensitization of the presynaptically located nicotinic receptors.…”
Section: Discussionmentioning
confidence: 88%
“…Interestingly, the facilitating effect on 3H-ACh release elicited by physostigmine 10 -4 M in AD/SDAT brain tissue, was partially blocked in the presence of d-tubocurarine 10 -6 M, indicating that the enhanced release might be induced via nicotinic receptors. This assumption is supported by the finding that nicotinic agonists can induce an increased release of 3H-ACh by stimulating nicotinic receptors (Beani et al, 1985). Presynaptic nicotinic receptors mediating a postive feedback on ACh release at the muscle endplate have also been suggested (Wessler et al, 1986;Vizi et al, 1987).…”
Section: Discussionmentioning
confidence: 94%
“…It has been suggested that this latter type of receptors might be present on the intracortical cholinergic nerve endings (Rowell & Winkler, 1984;Araujo et al, 1987). However, the antagonism by tetrodotoxin of the effect of nicotine on unstimulated guinea-pig cortical slices (Beani et al, 1985), together with some negative results on binding and biochemical studies on synaptosomes after lesioning of the subcortical cholinergic nuclei of the rat (Schwartz et al, 1984;Meyer et al, 1987), cast some doubts about such definite or exclusive localization. Further studies are needed to clarify if these supposed autoreceptors are also upstream (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Autoreceptors too seem to exist. This inference is based on binding studies carried out in human brains with spontaneous lesions of the basal cholinergic nuclei (Whitehouse et al, 1986;Nordberg & Winblad, 1986) and on neurochemical investigations performed in animal brain synaptosomes (Rowell & Winkler, 1984;Moss & Wonnacott, 1985) and cortical slices (Beani et al, 1985;Araujo et al, 1987). The actual relevance of nicotine-induced facilitation of acetylcholine (ACh) release remains, however, to be firmly established in physiological, integrated models.…”
Section: Introductionmentioning
confidence: 99%
“…These effects are most likely due to its interaction with specific brain receptors, which increase the firing rate and secretion of many neurones (Balfour, 1982). Nicotine increases 5-hydroxytryptamine (5-HT) and dopamine release (Westfall et al, 1983;Imperato et al, 1986;Balfour, 1989;Carboni et al, 1989;Riberio et al, 1993;Nisell et al, 1994) as well as acetylcholine release (Beani et al, 1985;Nordberg et al, 1989) both in vivo and in vitro preparations. Moreover, the drug increases excitatory amino acid outflow in vivo (Garza De La et al, 1989;Beani et al, 1991;Toth et al, 1993) and in vitro (Perez de la Mora et al, 1991).…”
Section: Introductionmentioning
confidence: 99%